Mineralogical characterization of the intraseam layers of Lofoi lignite deposits in Florina basin (western Makedonia, northwest Greece) - Oikonomopoulos, Ioannis K.; Tougiannidis, Nikolaos; Perraki, Theodora; Gurk, Marcus (Energy sources. Part A, Recovery, utilization, and environmental effects, 2016)
The mineralogical composition of intraseam layers from Lofoi lignite deposits (northwest Greece) is the subject of the present study. The samples were examined by means of X-ray diffraction (XRD), thermo-gravimetric (TG/DTG) and differential thermal analysis (DTA), and Fourier transform infrared (FT-IR) spectrometry. The clay minerals prevail in most samples, with illite-muscovite being the dominant phase, and kaolinite and chlorite being the other major clay components. No smectite was found. Quartz and feldspars, dominate in two cases. The studied materials are characterized as clays to clayey sands, showing significant similarities with the intraseam layers of the adjacent Achlada lignite deposits.